2019
DOI: 10.1021/acs.chemrev.9b00024
|View full text |Cite
|
Sign up to set email alerts
|

Approaches to Obtaining Fluorinated α-Amino Acids

Abstract: Fluorine does not belong to the pool of chemical elements that nature uses to build organic matter. However, chemists have exploited the unique properties of fluorine and produced countless fluoro-organic compounds without which our everyday lives would be unimaginable. The incorporation of fluorine into amino acids established a completely new class of amino acids and their properties, and those of the biopolymers constructed from them are extremely interesting. Increasing interest in this class of amino acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
107
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(107 citation statements)
references
References 357 publications
(384 reference statements)
0
107
0
Order By: Relevance
“…The Yu group found that isocyanides are also active in CÀ H activation reactions of indole-N-carboxamides (Scheme 27). [37] By treating indole-N-carboxamides or aza-indole-N-carboxamides 105 and tert-butyl isocyanide 106 with 5 mol % Pd 2 (dba) 3 at 60°C in methanol and air, a type of intriguing medicinally important imidazo[1,5-a]indole and pyrrolo[1,2-c]imidazole 107 could be constructed in good yields. Of note, when indole-Ncarboxamides were functionalized with various heteroaryl groups, corresponding products 110 bearing diverse heterocycles could be isolated efficiently.…”
Section: Reaction Of Indole-n-carboxamides With Other Compoundsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Yu group found that isocyanides are also active in CÀ H activation reactions of indole-N-carboxamides (Scheme 27). [37] By treating indole-N-carboxamides or aza-indole-N-carboxamides 105 and tert-butyl isocyanide 106 with 5 mol % Pd 2 (dba) 3 at 60°C in methanol and air, a type of intriguing medicinally important imidazo[1,5-a]indole and pyrrolo[1,2-c]imidazole 107 could be constructed in good yields. Of note, when indole-Ncarboxamides were functionalized with various heteroaryl groups, corresponding products 110 bearing diverse heterocycles could be isolated efficiently.…”
Section: Reaction Of Indole-n-carboxamides With Other Compoundsmentioning
confidence: 99%
“…They are easily found in the pages of commercial chemical supplier catalogs and widely used as versatile starting materials in various types of organic reactions. [3] Comparing with the common C-carboxylic acids, heteroatom-carboxylic acids (e. g. O-carboxylic acids and N-carboxylic acids) are relatively rarely studied, due to their common instability and hard preparation. [4] Indole-N-carboxylic acids are a type of intriguing N-carboxylic acids, which might serve as elegant reagents in the development of new indolesrelated reactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fluoroalkylation has become one of the most important approaches to incorporate fluorinated motifs with interesting topographies and physicochemical features and to desirably modulate the attributes of the target molecules. [6] With a deeper understanding of how to take full advantage of the unique nature of fluorine by chemists, deployment of late-stage fluoroalkylation in the construction of sophisticated compounds has emerged in the last decade.…”
Section: Introductionmentioning
confidence: 99%
“…Among the ethers, a-fluoroetherssuch as difluoromethylethers are important components because the introduction of fluorine atom(s) changes the chemical, physical, and biological properties of organic compounds. [1] For example, a-fluoroethersi mprovedt he lipophilicity andi nv ivo oxidative stabilityo fd rugs compared with alkyl ethers. [1a, 2] However,o nly al imited number of practical a-fluoroalkylations of aliphatic alcohols have been reported.…”
mentioning
confidence: 99%